Long-term care: Discussing distributional equity and equity of access in Austria - Schmidt, Andrea E.; Waitzberg, Ruth; Blümel, Miriam (Momentum Quarterly, 2021)
While costs of long-term care (LTC) are often discussed in public and in the media, little attention is usually paid to the issue of domestic, distributional equity of public funds for LTC. Against the background of an international comparison, two criteria of distributional equity in LTC in Austria are analysed: regional eligibility criteria and fair criteria for regional redistribution. The analysis illustrates that there is a need for improvement in Austria, especially with regard to the distribution of resources for in-kind benefits, i.e. the provision of professional LTC services and care services. A possible conclusion could refer to the development of a sustainable financing system as well as better coordination and a clear allocation of responsibilities for the costs of LTC, taking into account the perspective of those in need of care.
Keywords: long-term care; equity; distribution; equity of opportunity; funding